BUKTI-BUKTI KEILAHIAN DAN KEMANUSIAAN YESUS DALAM PERJANJIAN BARU - Adi Putra (STT Saint Paul Bandung, 2022)
This research examines the evidences of the divinity and humanity of Jesus in the New Testament. These two natures of Jesus have often been debated among Christians throughout the history of the church. Evidenced by the emergence of four popular views such as: ebionism, Arianism, docetism, apolinarism. By using qualitative research, the researcher examines, analyzes and elaborates literature, articles and studies from experts to find interpretations of the New Testament texts in order to produce valid and reliable views and be held as truth. The conclusion of this study is that the New Testament evidence shows that Jesus was true God and true man.